Structural adjustment programmes - an assessment. - Picciotto, Robert (1997)
Takes an objective look at how the structurla adjustment progrmmes supported by the World Bank have affected people and economies. Identifies some myths associated with adjustment lending. Concludes that economic growth has increased and poverty has declined in countries that have successfully implemented adjustment programmes.